Dendritic cell profiles in the inflamed colonic mucosa predict the responses to tumor necrosis factor alpha inhibitors in inflammatory bowel disease - Smrekar, Nataša (Radiology and oncology (Ljubljana), 2018)
Background Dendritic cells play crucial roles in the control of inflammation and immune tolerance in the gut. We aimed to investigate the effects of tumor necrosis factor alpha (TNFa) inhibitors on intestinal dendritic cells in patients with inflammatory bowel disease and the potential role of intestinal dendritic cells in predicting the response to treatment. Patients and methods Intestinal biopsies were obtained from 30 patients with inflammatory bowel disease before and after treatment with TNFa inhibitors. The proportions of lamina propria dendritic cell phenotypes were analysed using flow cytometry. Disease activity was endoscopically assessed at baseline and after the induction treatment. Results At baseline, the proportion of conventional dendritic cells was higher in the inflamed mucosa (7.8%) compared to the uninflamed mucosa (4.5%) (p = 0.003), and the proportion of CD103+ dendritic cells was lower in the inflamed mucosa (47.1%) versus the uninflamed mucosa (57.3%) (p = 0.03). After 12 weeks of treatment, the proportion of conventional dendritic cells in the inflamed mucosa decreased from 7.8% to 4.5% (p = 0.014), whereas the proportion of CD103+ dendritic cells remained unchanged. Eighteen out of 30 (60%) patients responded to their treatment by week 12. Responders had a significantly higher proportion of conventional dendritic cells (9.16% vs 4.4%, p < 0.01) with higher expression of HLA-DR (median fluorescent intensity MFI 12152 vs 8837, p = 0.038) in the inflamed mucosa before treatment compared to nonresponders. Conclusions A proportion of conventional dendritic cells above 7% in the inflamed inflammatory bowel disease mucosa before treatment predicts an endoscopic response to TNFa inhibitors.
Keywords: črevesna sluznica; dendritične celice; vnetje; vnetna črevesna bolezen; zdravljenje